Desenvolvimento inicial e densidade de estocagem de larvas de Aracu-riscado, Leporinus agassizii (Characiformes: Anostomidae) - Ferreira, Luana Malheiros [UNESP] (2015)
Studies for the production of young fish shapes are key to the development of fish farming and the management of natural populations. Leporinus agassizii is appreciated in the different fishing methods (commercial, craft, ornamental and sports), and present desirable features for creation. This study aimed to describe the embryonic and larval stocking density of aracu-riscado, L. agassizii. Players underwent reproduction induced hypophysation, with the water temperature at 28.6±0.7 °C, the Centro de Capacitação e Produção de Alevinos belonging to the Instituto Federal de Educação, Ciência e Tecnologia, São Gabriel da Cachoeira, Amazonas, Brazil, in September 2014. After fertilization, the eggs were kept in incubators (60 Litre), with the average water temperature of 28.4±0.7 °C. Samples were collected 10 min intervals on eggs during the first three hours after fertilization (AF) and thereafter at intervals of 30 minutes until the outbreak of the larvae, for observation in stereo equipped with digital color CMOS camera, 10.0 MP and software to capture and analyze images (ISCapture). The effect of larval stocking density of L. agassizii was assessed over 4th and 14th days after hatching (DAH). 3600 larvae were used in the 4th DAH, meeting these with the yolk sac fully absorbed, mouth open and fasted. The effect of larval stocking density of L. agassizii was assessed over 4th and 14th (DAH). 3600 larvae were used in the 4th DAH, meeting these with the yolk sac fully absorbed, mouth open and fasted. The larvae were subjected to density of 5 (D5), 15 (D15) and 25 (D25) larvas.L-1, in polyethylene boxes (0.63 x 0.45 x 0.32 m) with 20 Litre of water. We used a completely randomized design with four replications. The larvae were fed six times a day, each meal consisting of Artemia in the proportion 50 náuplios.larva-1 (4th to 6th DAH), 100 (7th to 9th DAH), 200 (10th to 11th DAH) and 400 (12th to 13th DAH) and commercial diet ...